Analysis of the Effect of Capital Expenditures, Economic Growth and Education Levels on Labor Absorption - Angga Bayu Nugroho; Usman Moonti (Jambura Equilibrium Journal, 2019)
This study aims to analyze the Influence of Capital Expenditures, Economic Growth and Education Levels on Labor Absorption in the District / City Region of Gorontalo Province. The data used is sourced from the Gorontalo Province Central Bureau of Statistics (BPS) during the period 2010-2015, SIMREG BAPPENAS. The estimation is done by the fixed effect model (FEM) method. The results showed that (i) the amount of Gorontalo Province Capital Expenditures had a negative but not significant effect on the amount of Absorption of Labor. (ii) The Economic Growth of Gorontalo Province has a negative and significant effect on the magnitude of the number of Labor Absorption. (iii) The level of education (measured by APM SMA) in Gorontalo Province has a positive and significant effect on the amount of Absorption of Labor